2008
DOI: 10.1021/jp711833k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Thiol-Tethered Tripyridyl Porphyrin on Au(111)

Abstract: Porphyrins are actively studied for use in molecular and organic electronic components of devices because of their diverse tunable optical and electronic properties. In this study, mixed self-assembled monolayers (SAMs) of dodecanethiol and a tripyridyl porphyrin attached to a thiol tether via a perfluorinated phenyl ring (TPy 3 PF 4 -SC 5 SH) were prepared on Au(111) substrates. The synthetic strategy allows for rapid formation of derivatives with different tethers. The surface structural and electronic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 98 publications
(136 reference statements)
8
62
0
Order By: Relevance
“…In these STM studies, molecules of interest have been inserted in an alkylthiol self-assembled monolayer (SAM). The observed stochastic conductance switching has been explained by conformational changes [7] like in more recent works using STM [2,8] or break junctions [1], or molecular hybridization changes at the interface with gold [9,10]. However, independent STM studies on SAMs on gold have reported similar stochastic switching effects for thiol molecules, which cannot exhibit any conformational changes [11].…”
mentioning
confidence: 72%
“…In these STM studies, molecules of interest have been inserted in an alkylthiol self-assembled monolayer (SAM). The observed stochastic conductance switching has been explained by conformational changes [7] like in more recent works using STM [2,8] or break junctions [1], or molecular hybridization changes at the interface with gold [9,10]. However, independent STM studies on SAMs on gold have reported similar stochastic switching effects for thiol molecules, which cannot exhibit any conformational changes [11].…”
mentioning
confidence: 72%
“…With the appropriate choice of mobile phase the target porphyrin was obtained in low but not unreasonable yields for this procedure. [12] Coordination of Ru(bipy) 2 Cl 2 to the pyridyl nitrogen atoms was accomplished by previously described procedures. [13] It has been noted that coordination of three Ru(bipy) 2 Cl 2 moieties to the pyridyl nitrogen atoms of a porphyrin is extremely difficult under refluxing conditions in acetic acid.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Three electrodes electrochemical cell with gold disk electrodes 1.6 mm diameter (Bioanalytical system, USA), Ag/AgCl (3 M NaCl saturated with AgCl) reference electrode and platinum counter electrode were used. CV and EIS experiments were carried out in argon saturated 0.1 M Na 2 SO 4 containing K 3 [Fe(CN) 6 ]/K 4 [Fe(CN) 6 ] (0.5 mM each) as the supporting electrolyte to examine the monolayer properties at 25 • C [28,29]. CV measurements were performed from −0.2 to 0.2 V at different scan rate in 0.1 M Na 2 SO 4 to find the differential capacitance Electrochemical impedance spectroscopy performed in 0.1 M Na 2 SO 4 by applying an AC impedance in a frequency range between 1 Hz and 100 kHz with a perturbation signal of 5 mV at 0 V [29,30].…”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…The electronic properties of single molecules or small groups of molecules have been studied by constructing different electrical test beds including electrical and mechanical break junctions [5,8], crosswire junctions [2], conducting-probe atomic force microscopy [28] and scanning tunneling microscopy (STM) [2][3][4][5][6][7][8]28]. STM is a powerful surface analysis technique, as it enables the observation of individual molecules with atomic resolution on surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation